Rothmans presents : American Accents - Geldzahler, Henry (s.l. : Rothmans)
Bolotowsky, Ilya ; Hague, Raoul ; Guston, Philip ; Ellsworth, Kelly ; Johns, Jasper ; Twombly, Cy ; Duff, John ; Mitchell, Joan ; Wilmarth, Christopher ; Jess ; Warhol, Andy ; Stella, Frank ; Hendler, Maxwell ; Thiebaud, Wayne ; Price, Ken ; Hurson, Michael ; Sonnier, Keith; Lichtenstein, Roy ; Heizer, Michael ; Graves, Nancy ; Rothenberg, Susan
boek